The good detective [large type] - McMahon, John, 1970- (McMahon, John, 1970- Detective P.T. Marsh, 2019)
"Detective P.T. Marsh was a rising star on the police force of Mason Falls, Georgia, but since his wife and young son died in an accident he has made some disastrous decisions. His newest murder case is the man he beat up the night before, and that man may be the number one suspect in another murder"--